Exogenous Methyl Jasmonate Application Improved Physio-Biochemical Attributes, Yield, Quality, and Cadmium Tolerance in Fragrant Rice - Kanu, Adam Sheka; Ashraf, Umair; Mansaray, Lamin R.; Abbas, Farhat; Fiaz, Sajid; Amanullah, Sikandar; Charley, Christen Shaka; Tang, Xiangru (Frontiers in Plant Science, 2022)
Cadmium (Cd) has detrimental effects on crop plants, whereas, jasmonates (JAs) play a vital role in abiotic stress tolerance in plants. The present study investigated the effects of exogenous application of methyl jasmonate (MeJa) on the physio-biochemical attributes, yield, and quality of two fragrant rice cultivars, i.e., Xiangyaxiangzhan and Meixiangzhan-2 under Cd stress. The experiment was comprised of four treatments, i.e., CK, control (normal conditions); Cd: 100 mg Cd kg–1 of soil; MeJa: exogenous application of MeJa at 20 mM; and Cd + MeJa: 100 mg Cd kg–1 of soil + exogenous MeJa application at 20 mM. Results depicted that Cd toxicity resulted in a substantial reduction of enzymatic activities and non-enzymatic antioxidants, chlorophyll contents, while enhanced oxidative damage in the terms of lipid peroxidation (higher malondialdehyde (MDA) contents), H2O2, and electrolyte leakage. Proline contents were found higher whereas protein and soluble sugars were lower under Cd stress as compared with Ck and Cd + MeJa. Exogenous MeJa application further improved the panicles per pot, spikelets per panicle, seed setting (%), 1,000 grain weight, and yield per pot under Cd stress conditions as compared with non-MeJa applied plant under Cd stress. In addition, exogenous MeJa application enhanced the accumulation of macro (N, P, K, Mg, and Ca) and micronutrients (Mn, Zn, Fe, and Cr) in both cultivars under Cd stress, while reduced the Cd contents in different plant parts. Overall, the contents of Cd in different plant organs were recorded as: root > stem > leaves > grains for all treatments. Comparing both cultivars, the grain Cd contents were higher in Meixiangzhan 2 than Xiangyaxianzhan under Cd contaminated conditions. Conclusively, Cd toxicity impaired growth in rice by affecting physio-biochemical attributes, however, Xiangyaxiangzhan performed better than Meixiangzhan-2 cultivar.